KAJIAN FORMULASI PUREE DAGING DAN PUREE EMPULUR NANAS (ANANAS COMOSUS (L) MERR) DALAM PEMBUATAN COOKIES - rikawati, andina may (Fakultas Pertanian Universitas Tanjungpura, 2019)
Pineapple is one of fruit that has a specific flavor and usually consumed fresh. It also has a short shelf-life, therefore it is necessary to be diversified. Generally, cookies are made from low protein flour so that it can be formulated with other ingredients.The ingredients added are pineapple flesh puree and pineapple pith puree which has high content of fiber and beneficial for helping the digestive process. This study aimed to determine the comparison between cookies formulations which made from different levels of pineapple components puree, namely flesh and pith based on physicochemical and sensory characteristics.This study used a randomized block design (RBD) with one treatment factor, which was a comparison between flesh and pith pineapple puree consists of 6 levels.The results showed that the best cookie formulation was at 75 % puree of flesh and 25 % puree of pineapple pith with moisture content at 2.42 %, ash content at 0.99 %, crude fiber 2.54 %, texture at 0.13 %, protein content 7.1 %, fat content 35.41 %, and carbohydrate 54.56 %.The best characteristic cookies based on sensory were hardness 3.93 (quite crunchy), flavor 2.60 (less acidic), aroma 2.77 (lack of fruit aroma), color of 3.43 (quite yellow), and preference of 3.70 (quite like it).The formulation of flesh puree and pineapple pith puree that the panelists like, does not affect the overall preference for the cookies produced. keyword : pineapple, cookies, fiber, puree, formulation